Atypical sensors for direct and rapid neuronal detection of bacterial pathogens. Issue 1 (December 2016) - Lim, Ji; Choi, Seung-In; Choi, Geunyeol; Hwang, Sun
Abstract Bacterial infection can threaten the normal biological functions of a host, often leading to a disease. Hosts have developed complex immune systems to cope with the danger. Preceding the elimination of pathogens, selective recognition of the non-self invaders is necessary. At the forefront of the body's defenses are the innate immune cells, which are equipped with particular sensor molecules that can detect common exterior patterns of invading pathogens and their secreting toxins as well as with phagocytic machinery. Inflammatory mediators and cytokines released from these innate immune cells and infected tissues can boost the inflammatory cascade and further recruit adaptive immune cells to maximize the elimination and resolution. The nervous system also seems to interact with this process, mostly known to be affected by the inflammatory mediators through the binding of neuronal receptors, consequently activating neural circuits that tune the local and systemic inflammatory states. Recent research has suggested new contact points: direct interactions of sensory neurons with pathogens. Latest findings demonstrated that the sensory neurons not only share pattern recognition mechanisms with innate immune cells, but also utilize endogenous and exogenous electrogenic components for bacterial pathogen detection, by which the electrical firing prompts faster information flow than what could be achieved when the immune system is solely involved. As a result, rapid pain generation and active accommodation of the immune status occur. Here we introduced the sensory neuron-specific detector molecules for directly responding to bacterial pathogens and their signaling mechanisms. We also discussed extended issues that need to be explored in the future.